Assimilating Islamic Banking Customer Loyalty: A Halal Brand Personality Perspective Model - Raden Roro Fosa Sarassina; Reni Furwanti; Dini Maulana Lestari (Faculty of Economic and Business, 2023)
As Indonesian government promotes Indonesia as the center of the Halal Industry Nation, numerous strategies are being implemented across every sector, including Islamic Financial Institution. This research focuses investigating factors that can influence customer loyalty. To bridge this gap, the study aims to create a model for increasing customer loyalty based on the Halal Brand Personality approach, by exploring competitive advantage as a mediating variable. This research is considered important due to the relatively small market share of Islamic banking in Indonesia, which faces intense competition. This is an explanatory research with a quantitative approach that employs survey method to collect 225 data points. Structural Equation Modeling (SEM) is used to analyze the direct and indirect relationship of each variable. It was found that from all the hypotheses, six were rejected, and the model was validated. The result delineated that the model proposed in this research can assist branch managers in maximizing and strengthening Islamic banking’s distinctive products and sophisticated technology, which are its primary competitive advantages when competing with other banking sectors.JEL Classification: M20, M21, M31How to Cite:Sarassina, R. R. F., Furwanti, R., & Lestari, D. M., (2023). Assimilating Islamic Banking Customer Loyalty: A Halal Brand Perspective Model. Etikonomi, 22(2), 247 – 262. https://doi.org/10.15408/etk.v22i2.31566.